ANALISIS PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS: STUDI KASUS PADA RUMAH SAKIT X - Ayuntari, Chivalrind G; Wahyuningrum, Dwi Sari (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to analyze the effect of working capital management on profitability in X Hospital. The research method used is descriptive quantitative. The data source used comes from secondary data in the form of financial statements of Hospital X for the period 2020 - 2022.  Working capital analysis is carried out by analyzing financial ratios using cash turnover, accounts receivable turnover, and inventory turnover ratios. Meanwhile, to analyze profitability, the ratios of return on assets (ROA), return on equity (ROE,) and net profit margin (NPM) were used. The results showed that working capital management has a significant effect on profitability